Electronic differential system for an electric vehicle with In-wheel motor - Yıldırım, Merve; Öksüztepe, Eyyüp; Tanyeri, Burak; Kürüm, Hasan (My University, 2015)
This paper presents modeling and simulation of Electronic Differential System (EDS) for the dual-front-wheel independently driven Electric Vehicle (EV). Electronic differential is utilized in EVs due to some drawbacks of traditional mechanical differential such as being heavy and bulky systems which are not convenient for EV, and mechanical losses caused by the powertrains. In this study, an EDS for front wheels of an EV with in-wheel motor is modelled instead of rare wheels which has commonly been studied in the literature. The front wheel speeds are estimated by equations derived from Ackermann-Jeantand model using Codesys Software Package. Then, the simulation of EDS is also realized by Matlab/Simulink. According to the change of the vehicle speed and steering angle of EV, front wheel speeds estimated by Codesys are verified by Simulink results. It is observed that the modelled EDS is appropriate for EVs with in-wheel motors.
Bildiri - Yayımlanmamış
Keywords: Electric vehicle; In-wheel motor; Electronic differential system